Efficient red organic light-emitting diode based on simple Pt(II) OˆN- complex. (December 2016) - Taydakov, Ilya; Lyssenko, Konstantin; Saifutyarov, Rasim; Akkuzina, Alina; Avetisov, Roman; Mozhevitina, Alena; Avetissov, Igor
Abstract: A first observation of red-orange electroluminescence (CIE chromacity coordinates X = 0.5389, Y = 0.3842) of platinum(II) bis-(8-hydroxyquinolinate) incorporated in multilayer OLED structure as a dopant component of the emission layer was made. It was estimated, that high chemical purity of abovementioned complex is vital for good electroluminescence properties. Besides, new reliable synthetic pathways to PtQ2 have been developed, and its photophysical properties have been investigated. Graphical abstract: Highlights: First PtQ2 -based OLED structure with high brightness efficiency was produced. Improved synthetic pathways of platinum(II) bis-(8-hydroxyquinolinate) was developed. 99.9922 wt% PtQ2 photoluminescence was studied.